Frequency and Causes of False-Positive Elevated Plasma Concentrations of Fasting Gut Hormones in a Specialist Neuroendocrine Tumor Center - Butler, Olivia L.; Mekhael, Monica M.; Ahmed, Arslan; Cuthbertson, Daniel J.; Pritchard, D. Mark (Frontiers in Endocrinology, 2020)
Introduction: In the UK, the fasting plasma concentrations of a panel of gut hormones (comprising vasoactive intestinal peptide (VIP), gastrin, pancreatic polypeptide (PP), glucagon, somatostatin and chromogranin A) are measured to evaluate patients who have or who (due to unexplained and compatible symptoms) are suspected of having neuroendocrine tumours (NETs). False positive elevated hormone concentrations are sometimes found. Objective: To evaluate the frequency and implications of false positive fasting gut hormone results. Methods: Retrospective audit of fasting gut hormone profile results at a large UK university teaching hospital over 12 months. Results: Fasting gut hormone concentrations were measured in 231 patients during 2017. No NETs were found in the 88 patients who had this test performed only to investigate symptoms. 31 false positive gastrin, 8 false positive chromogranin A, 2 false positive glucagon, 3 false positive somatostatin, 1 false positive PP and 1 false positive VIP results were found. We extended the audit for glucagon and somatostatin for an additional two years and found 7 probable false-positive raised glucagon concentrations and 4 probable false-positive elevated plasma somatostatin concentrations in total. Conclusions: False-positive elevations of plasma gastrin and chromogranin A were common and causes such as proton pump inhibitor use or inadequate fasting accounted for most cases. Elevated plasma concentrations of the other gut hormones were also detected in patients who had no other evidence of NET. Other diagnoses (e.g. cirrhosis and medullary thyroid carcinoma for hypersomatostatinaemia and type 2 diabetes mellitus, pancreatitis, liver or renal impairment for hyperglucagonaemia) may cause these false positive results.